PERSEPSI PEMUDA TANI TERHADAP PEKERJAAN SEBAGAI PETANI DI KECAMATAN PURWOREJO KABUPATEN PURWOREJO - Elya Fitriyana; Arip Wijianto; Emi Widiyanti (Universitas Sebelas Maret, 2018)
This research was aimed to investigate the perception of youth farmers to farmer's job, to investigate the factor of perception formers, and to investigate the relationship of perception-formers factors with the perception of youth to farmer's job. The basic method used was descriptive analysis with survey technique. The location of research was determined purposively that is Purworejo Subdistrict Purworejo District. The sample was determined by multistage cluster random sampling technique, as many as 60 youth farmers scattered in three villages namely Pacekelan Village, Ganggeng Village, and Paduroso Village. Data analysis used spearman rank. The results showed that the perception of youth to farmers’ job is 66.67% that youth have good perception on the farmers' job. The factors forming the perception of youth farmers in Purworejo sub district are majority of formal education in the high category, the majority of family environment in the medium category, majority social culture in low category, whereas non-formal education, primary social environment, secondary social environment and cosmopolitan majority in category very low. There is an intense significant relationship between family environment and socio-culture with youth perception on farmer's work at 99% confidence level, at 95% level there is a significant relationship between work involvement and primary social environment with youth perception on farmer's job, whereas formal education, non-formal education, secondary social and cosmopolitan environments do not have a significant relationship with youth perceptions of farmer's job.